The role of SWI/SNF chromatin remodelers in the repair of DNA double strand breaks and cancer therapy - Sadek, Maria; Sheth, Anand; Zimmerman, Grant; Hays, Emily; Vélez-Cruz, Renier (Frontiers in Cell and Developmental Biology, 2022)
SWI/SNF chromatin remodelers hydrolyze ATP to push and slide nucleosomes along the DNA thus modulating access to various genomic loci. These complexes are the most frequently mutated epigenetic regulators in human cancers. SWI/SNF complexes are well known for their function in transcription regulation, but more recent work has uncovered a role for these complexes in the repair of DNA double strand breaks (DSBs). As radiotherapy and most chemotherapeutic agents kill cancer cells by inducing DSBs, by identifying a role for these complexes in DSB repair we are also identifying a DNA repair vulnerability that can be exploited therapeutically in the treatment of SWI/SNF-mutated cancers. In this review, we summarize work describing the function of various SWI/SNF subunits in the repair of DSB with a focus on homologous recombination repair and discuss the implication for the treatment of cancers with SWI/SNF mutations.